Fuzzy Model-Based Asynchronous Control for Markov Switching Systems with Stochastic Fading Channels - Fayuan Wu; Jinhui Tang; Zhuang Liu; Qi Xiao; Xiaodong Zheng; Shuangsi Xue (Complexity)
This work investigates the asynchronous control for fuzzy Markov switching systems (MSSs) with randomly occurring fading channel. By resorting to a T-S fuzzy model, the nonlinear MSSs can be handled. Meanwhile, in the unreliable network, the Rice fading model is proposed to capture the randomly occurring channel fading, which covers packet dropouts and network-induced delays as special cases. In light of the hidden Markov model, the asynchronous phenomenon of controller is taken into consideration, and asynchronous fuzzy controller is obtained. In the end, a numerical example and a single-link robotic arm model are applied to demonstrate the validity of the derived results.